Heliotropium curassavicum extract: Potential therapeutic agent for liver cancer through cytotoxicity, apoptosis, and molecular docking analysis - Nael Abutaha; Raed Alghamdi; Omair Alshahrani; Muhammad Al- Wadaan (Arabian Journal of Chemistry, 2024)
Hepatocellular carcinoma is the fifth most common cancer worldwide, posing significant challenges due to drug resistance and adverse effects associated with current treatments. Plant extracts, known for their diverse bioactive compounds, offer promising alternatives for cancer treatment. The study aimed to investigate the potential of Heliotropium curassavicum by extracting its phytochemicals through Soxhlet extraction and maceration methods. The study also aimed to assess in-vitro cytotoxicity using the MTT assay, evaluate cell migration using scratch, and analyse apoptosis using fluorescent microscopy. Additionally, GC–MS analysis was performed to identify chemical compounds and in-silico analysis was conducted to predict the most potent anticancer compounds in the extracts. Only the maceration method using n-hexane (F4) and ethyl acetate extract (F5) showed cytotoxic activity against HuH7, HepG2, and MDA-MB-231. The F4 showed cytotoxic activity with IC50 values of 93.9, 121.7, and 142.2 µg/mL, respectively. Similarly, the F5 demonstrated cytotoxic effects with IC50 values of 144 µg/mL for HuH7, 74 µg/mL for HepG2, and 150 µg/mL for MDA-MB-231. The wound-healing assay demonstrated that the F5 extract significantly reduced the migration of HepG2 cells. Based on the acridine orange/ethidium bromide and DAPI staining, the F5 fraction exhibited apoptotic potential in HepG2 cells. In GC–MS analysis, 33 phytocompounds were identified in the F5 fraction, from which 9 compounds were chosen for drugability studies. Among them, phytol and oleic acid were the only ones that showed no hepatotoxicity, neurotoxicity, nephrotoxicity, cardiotoxicity, immunotoxicity, or carcinogenicity. Molecular docking studies revealed that phytol and oleic acid had the strongest binding affinities of −8.5 and −7.6 kcal/mol against 6OOY, respectively. This is followed by −7.2 kcal/mol (phytol) and −7.1 kcal/mol (oleic acid) against 1UOM. The phytochemicals identified in the F5 fraction demonstrate significant potential as therapeutic candidates for liver cancer, necessitating further investigation through additional studies.